2018
DOI: 10.1080/17436753.2018.1508625
|View full text |Cite
|
Sign up to set email alerts
|

Fracture resistance of endodontically treated maxillary incisors restored with zirconia posts: effect of the internal plateau preparation

Abstract: We report on a new approach to increase the fracture resistance of endodontically treated teeth. We propose a preparation of horizontal internal plateau (IP) in dentine and the use of retentive zirconia posts to achieve a more favourable load transmission. The aim of our work was to investigate the effect of the IP depth and the post diameter on the fracture resistance and the failure mode of maxillary central incisors. Seventy-two teeth were, divided into six groups of 12. IP 4 mm in diameter and 0, 1 or 2 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This study, followed the post diameters given in the literature. Within these limits, although not statistically significant, post diameter was more effective than post length in Group Z unlike Group F and Group P. In a study published in 2019, two different diameters of prefabricated zirconia posts were used, and although the fracture strength of the wide diameter post was high, this difference was not found to be significant 35 …”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This study, followed the post diameters given in the literature. Within these limits, although not statistically significant, post diameter was more effective than post length in Group Z unlike Group F and Group P. In a study published in 2019, two different diameters of prefabricated zirconia posts were used, and although the fracture strength of the wide diameter post was high, this difference was not found to be significant 35 …”
Section: Discussionmentioning
confidence: 82%
“…Within these limits, although not statistically significant, post diameter was more effective than post length in Group Z unlike Group F and Group P. In a study published in 2019, two different diameters of prefabricated zirconia posts were used, and although the fracture strength of the wide diameter post was high, this difference was not found to be significant. 35 Studies investigating the effect of the length of the fibre post on fracture resistance have shown that it does not make a significant difference. [36][37][38][39] However, some studies have reported that the fracture resistance of short glass-fibre posts was significantly higher.…”
Section: Ta B L E 2 Means and Standard Deviationsmentioning
confidence: 99%